Approaches to formalization of the informal waste sector into municipal solid waste management systems in low- and middle-income countries: Review of barriers and success factors. (March 2017) - Aparcana, Sandra
Highlights: The type of formalization does not of itself ensure the success in the long term. Policy, economic, and institutional measures are key factor in formalization. The acknowledgment of the contribution of formalized recyclers is a key factor. Country or local policies for other sector can hamper a successful formalization. Unawareness of the interactions between measures may lead formalization to fail. Abstract: Background and goal: The Municipal Solid Waste Management (MSWM) sector represents a major challenge for low-and middle-income countries due to significant environmental and socioeconomic issues involving rapid urbanization, their MSWM systems, and the existence of the informal waste sector. Recognizing its role, several countries have implemented various formalization measures, aiming to address the social problems linked to this sector. However, regardless of these initiatives, not all attempts at formalization have proved successful due to the existence of barriers preventing their implementation in the long term. Along with this, there is a frequent lack of knowledge or understanding regarding these barriers and the kind of measures that may enable formalization, thereby attaining a win-win situation for all the stakeholders involved. In this context, policy- and decision-makers in the public and private sectors are frequently confronted with the dilemma of finding workable approaches to formalization, adjusted to their particular MSWM contexts. Building on the review of frequently implemented approaches to formalization, including an analysis of the barriers to and enabling measures for formalization, this paper aims to address this gap by explaining to policy- and decision-makers, and to waste managers in the private sector, certain dynamics that can be observed and that should be taken into account when designing formalization strategies that are adapted to their particular socioeconomic and political-institutional context. This includes possible links between formalization approaches and barriers, the kinds of barriers that need to be removed, and enabling measures leading to successful formalization in the long term. Method: This paper involved a literature review of common approaches to formalization, which were classified into three categories: (1) informal waste workers organized in associations or cooperatives; (2) organized in CBOs or MSEs; and (3) contracted as individual workers by the formal waste sector. This was followed by the identification and subsequent classification of measures for removing common barriers to formalization into five categories: policy/legal, institutional/organizational, technical, social, and economic/financial. The approaches to formalization, as well as the barrier categories, were validated through the assessment of twenty case studies of formalization. Building on the assessment, the paper discussed possible links between formalization approaches and barriers, the 'persistent' challenges that represent barriers to formalization, as well as key enabling factors improving the likelihood of successful formalization. Results: Regardless of the type of approach adopted to formalization, the review identifies measures to remove barriers in all five categories, with a stronger link between the approaches 1 and 2 and the existence of measures in the policy, institutional, and financial categories. Regarding persistent barriers, the review identified ones arising from the absence of measures to address a particular issue before formalization or due to specific country- or sector-related conditions, and their interaction with the MSWM context. 75% of the case studies had persistent barriers in respect of policy/legal issues, 50% of institutional/organizational, 45% of financial/economic, and 40%, and 35% of social and technical issues respectively. Conclusions: This paper concludes that independently of the formalization approach, the lack of interventions or measures in any of the five categories of barriers may lead formalization initiatives to fail, as unaddressed barriers become 'persistent' after formalization is implemented. Furthermore, 'persistent barriers' may also appear due to unfavorable country-specific conditions. The success of a formalization initiative does not depend on a specific approach, but most likely on the inclusion of country-appropriate measures at the policy, economic and institutional levels. The empowerment of informal waste-workers is again confirmed as a further key success factor for their formalization.